Comparison between visual prostate symptom score and flow rate in benign prostatic hyperplasia (BPH) : a cross sectional study - Kathiresan, Narayanan (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Objective: To determine the correlation between visual prostate symptom score that is filled up without assistance and uroflowmetry (Qmax) among BPH patients undergoing treatment in Urology Clinic in a tertiary centre in Malaysia. Methodology: Ours is a cross sectional study done in a tertiary hospital in Kuantan, Malaysia.74 adult male patients who is under urology clinic follow up for benign prostatic hyperplasia were recruited and filled up the Visual Prostate Symptom Score sheet without assistance from medical personnel. Results were compared with Qmax values from uroflowmetry which is the routine measurement done in urology clinics to determine correlation with VPSS scores. Results: Pearson correlation was done to compare total VPSS score and Qmax. Our results show a weak correlation between VPSS total score and Qmax. (r=-0.149, p=0.205) that is not significant. We have done a subgroup analysis on age and education status and results did not correlate for all the subgroups. Conclusion: This study found that VPSS is not suitable to be filled up by patients on their own without medical practitioner assistance. We would recommend VPSS be filled up with assistance.